2007
DOI: 10.2471/blt.05.026153
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus (HIV) infection patterns and risk behaviours in different population groups and provinces in Viet Nam

Abstract: The finding of marked geographical variation in HIV prevalence underscores the value of understanding local contexts in the prevention of HIV infection. Although lacking support from data from all provinces, there would appear to be a potential for sex work to drive a self-sustaining heterosexual epidemic. That the close links to serious injecting drug use epidemics can have an accelerating effect in increasing the spread of HIV merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…In general, the results of this study indicate high rates of risky sexual behaviors among immigrants, including having multiple (concurrent) sexual partners and unprotected sexual intercourse, consistently with other research conducted in Europe [6,31] and in other regions [9,29,32,33]. These findings highlight the potential increasing risk for HIV infection of migrants who have unprotected sex with multiple sexual partners, but also if they acquire HIV/AIDS the increasing likelihood of transmitting HIV infection to their partners.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the results of this study indicate high rates of risky sexual behaviors among immigrants, including having multiple (concurrent) sexual partners and unprotected sexual intercourse, consistently with other research conducted in Europe [6,31] and in other regions [9,29,32,33]. These findings highlight the potential increasing risk for HIV infection of migrants who have unprotected sex with multiple sexual partners, but also if they acquire HIV/AIDS the increasing likelihood of transmitting HIV infection to their partners.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to findings among female sex workers in Vietnam, where drug use played a very important role in HIV transmission in this high-risk population [12, 37, 38]. This study also supports the evidence of the protective role of condom use in preventing HIV transmission among MSM.…”
Section: Discussionsupporting
confidence: 90%
“…Dong Nai borders with Hochiminh City, which has amongst the highest prevalence of HIV in Vietnam in all high-risk groups, including those who inject drugs, MSM, and female sex workers. Previous studies among MSM in Vietnam were carried out in urban populations, whereas our study was conducted in rural or small urban areas, except for Dong Nai which is an industrial province where HIV prevalence may be lower [8, 12]. The prevalence of HIV in the current study, 2.6 %, was lower than in other countries, including 13.6 % in Brazil [13], 12.9 % in northern Thailand [14], and 4.8 % in Beijing, China [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our review found that IDU comprised only a small proportion of HIV-infected TB patients in An Giang. Although this finding may be attributable to under-reporting, low rates of reported IDU are plausible, because this province is located far from large urban centers where injection drug use is more common [18]. Second, the vast majority of cases were smear-positive, which is uncommon in most HIV epidemic settings.…”
Section: Discussionmentioning
confidence: 93%